Crystal form of pyridinopyrazole derivative as well as preparation method and application of crystal form

By developing crystal forms of salts or eutectics formed by the compound of formula (I) with different acids, the problem of lack of effective USP1 inhibitors in the prior art is solved, and the significant inhibition of USP1 is achieved, and the application value of the tumor treatment is potential. .

CN119431367APending Publication Date: 2025-02-14TIBET HAISCO PHARM CO LTD

Patent Information

Application Number
CN202411031457.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-31
Filing Date
2024-07-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The lack of effective USP1 inhibitors in the prior art is unable to effectively regulate the DNA damage-repair pathway, resulting in tumor cell survival and replication fork degradation problems.

Method used

Develop a crystalline form of a salt or eutectic of the compound of formula (I) by combining para-hydroxybenzoic acid, benzoic acid, D(+)-10-camphorsulfonic acid, 3,5-dihydroxybenzoic acid, mandelic acid, Methanesulfonic acid, sulfuric acid, hydrochloric acid, hydrobromide, benzenesulfonic acid or 1,5-naphthalene disulfonic acid form different crystal forms, significantly improving the inhibitory activity of USP1.

Benefits of technology

The crystal form of the salt or eutectic of this compound shows significant USP1 inhibitory activity, with potential application prospects for the treatment of solid tumors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431367A_ABST
    Figure CN119431367A_ABST
Patent Text Reader

Abstract

The invention provides a crystal form of a salt or eutectic of a pyridinopyrazole derivative (a compound as shown in a formula (I)), a preparation method of the crystal form, and application of the crystal form and the preparation method in preparation of related medicines. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a crystal form of a salt or cocrystal of a compound, a preparation method and application thereof, and in particular to a crystal form of a salt or cocrystal of a pyridopyrazole derivative, a preparation method and application thereof, belonging to the technical field of pharmaceutical chemistry. Background Art

[0002] Protein ubiquitination in cells is a key protein modification that regulates multiple cellular processes. Protein ubiquitination is controlled by the synergistic action of E3 ubiquitin ligases and deubiquitinating enzymes (DUBs). DUBs can cleave the isopeptide bond between ubiquitin and the modified protein, and are responsible for removing ubiquitin from the target protein and rescuing it from the degradation pathway; they are also involved in the editing, maturation, and recycling of ubiquitin molecules after degradation. Currently, more than 100 deubiquitinating enzymes are known, and these proteins are subdivided into six subfamilies. The ubiquitin-specific protease (USP) subfamily is the largest subfamily, with 58 members currently known. USP is a cysteine ​​protease that contains a highly conserved catalytic domain, and USP1 is a member of the USP subfamily among DUBs.

[0003] Fanconi Anemia (FA) and DNA Translesion Synthesis (TLS) pathways were the first DNA damage tolerance and repair pathways discovered to be regulated by reversible ubiquitination. USP1 can regulate the deubiquitination of specific proteins in the FA and TLS pathways to participate in the regulation of DNA damage-repair pathways. USP1 plays an important role in DNA repair in tumor cells. It has been reported that the loss of USP1 leads to reduced survival and replication fork degradation in BRCA1-deficient cells. UAF1 (USP1-associated factor 1), as an auxiliary factor of USP1, USP12 and USP46, can enhance their deubiquitinase activity by forming a stable USP / UAF1 protein complex; the USP1 / UAF1 complex deubiquitinates a variety of substrates and is related to the regulation of DNA repair processes, tumor pathogenesis and antiviral innate immunity. Currently, there are no drugs targeting USP1 protein on the market, and the research on USP1 inhibitors has broad application prospects.

[0004] Patent PCT / CN2023 / 076700 discloses a compound of formula (I), which has good USP1 inhibitory activity.

[0005]

[0006] The present invention describes a crystal form of a salt or co-crystal of a compound of formula (I), which belongs to a USP1 inhibitor and is intended to be used for treating solid tumors. A preparation method is also disclosed. Summary of the invention

[0007] The present invention provides a salt or co-crystal of a compound represented by formula (I) in a crystalline form and a preparation method thereof, as well as their use in pharmaceutical compositions and in medicine.

[0008] The present invention provides a crystalline form of a salt or co-crystal of a compound of formula (I):

[0009]

[0010] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.45°±0.2°, 11.77°±0.2°, 11.98°±0.2°, 13.90°±0.2°, 16.39°±0.2°, 17.48°±0.2°, 18.30°±0.2°, 19.23°±0.2°, 19.44°±0.2°, 19.81°±0.2°, 20.05°±0.2°, 23.76°±0.2°, 24.44°±0.2°, 25.10°±0.2°, and 25.91°±0.2°.

[0011] In certain specific embodiments, the crystalline form is a crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.45°±0.2°, 11.77°±0.2°, 11.98°±0.2°, 12.48°±0.2°, 13.90°±0.2°, 16.39°±0.2°, 17.4 8°±0.2°, 18.30°±0.2°, 19.23°±0.2°, 19.44°±0.2°, 19.81°±0.2°, 20.05°±0.2°, 21.97°±0.2°, 22.44°±0.2°, 23.76°±0.2°, 24.44°±0.2°, 25.10°±0.2°, 25.91°±0.2°, 27.02°±0.2°.

[0012] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Figure 2 shown.

[0013] In a specific embodiment, the differential scanning calorimetry (DSC) curve of the crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid shows exothermic signals accompanied by endothermic signals at 174°C and 179°C, and a melting endothermic peak at about 193°C. Its thermogravimetric analysis (TGA) curve shows that the sample has no obvious weight loss during heating to 150°C, and continues to lose weight after 200°C, such as Figure 1 shown.

[0014] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.87°±0.2°, 17.05°±0.2°, 19.07°±0.2°, and 19.50°±0.2°.

[0015] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.87°±0.2°, 11.26°±0.2°, 11.67°±0.2°, 13.57°±0.2°, 17.05°±0.2°, 18.20°±0.2°, 18.51°±0.2°, 19.07°±0.2°, 19.50°±0.2°, 21.78°±0.2°, and 22.20°±0.2°.

[0016] In a specific embodiment, the crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid, using Cu-Kα radiation, has an X-ray powder diffraction pattern substantially as follows Figure 4 shown.

[0017] In a specific embodiment, the differential scanning calorimetry curve (DSC) of the crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid shows an endothermic signal peak accompanied by an exothermic signal peak at 130-180°C, a melting endothermic peak at about 192°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 3.5% of its weight during heating to 160°C, and continues to lose weight after 200°C, such as Figure 3 .

[0018] In certain specific embodiments, the crystalline form is crystalline form C formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.86°±0.2°, 11.10°±0.2°, 11.53°±0.2°, 16.76°±0.2°, 18.55°±0.2°, 18.76°±0.2°, 19.07°±0.2°, 19.29°±0.2°, 21.08°±0.2°, 21.66°±0.2°, 21.91°±0.2°, and 22.11°±0.2°.

[0019] In certain specific embodiments, the crystalline form is a crystalline form C formed by the compound of formula (I) and p-hydroxybenzoic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 3.86°±0.2°, 7.68°±0.2°, 11.10°±0.2°, 11.53°±0.2°, 16.76°±0.2°, 18.30°±0.2 °, 18.55°±0.2°, 18.76°±0.2°, 19.07°±0.2°, 19.29°±0.2°, 19.56°±0.2°, 21.08°±0.2°, 21.29°±0.2°, 21.66°±0.2°, 21.91°±0.2°, 22.11°±0.2°, 23.68°±0.2°, and 27.39°±0.2°.

[0020] In a specific embodiment, the crystalline form is a crystalline form C formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows: Figure 6 shown.

[0021] In a specific embodiment, the crystal form is crystal form C formed by the compound of formula (I) and p-hydroxybenzoic acid, and its differential scanning calorimetry analysis curve (DSC) shows an endothermic signal peak corresponding to TGA weight loss at 120-170°C, and a melting endothermic peak at about 192°C. The thermogravimetric analysis curve (TGA) shows that the sample has an 8.9% weight loss during heating to 160°C, and continues to lose weight after 160°C, as shown in 5.

[0022] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and benzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.16°±0.2°, 5.39°±0.2°, 8.33°±0.2°, 10.15°±0.2°, 14.74°±0.2°, 15.23°±0.2°, 16.49°±0.2°, 17.32°±0.2°, 21.00°±0.2°, and 22.75°±0.2°.

[0023] In certain specific embodiments, the crystalline form is a crystalline form A formed by the compound of formula (I) and benzoic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.16°±0.2°, 5.39°±0.2°, 8.33°±0.2°, 10.15°±0.2°, 11.92°±0.2°, 14.53 °±0.2°, 14.74°±0.2°, 15.23°±0.2°, 16.49°±0.2°, 17.32°±0.2°, 17.91°±0.2°, 21.00°±0.2°, 21.37°±0.2°, 21.76°±0.2°, 22.44°±0.2°, 22.75°±0.2°, 22.94°±0.2°.

[0024] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and benzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Figure 8 shown.

[0025] In a specific embodiment, the crystal form is a crystal form A formed by the compound of formula (I) and benzoic acid, and its differential scanning calorimetry curve (DSC) shows two endothermic signals at about 170°C and 179°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 0.4% during heating to 120°C and a weight loss of 11.2% during heating from 120 to 210°C, which may correspond to the process of decomposition of the benzoic acid eutectic and removal of benzoic acid, such as Figure 7 shown.

[0026] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 12.48°±0.2°, 18.33°±0.2°, and 19.75°±0.2°.

[0027] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 7.61°±0.2°, 12.48°±0.2°, 14.97°±0.2°, 15.15°±0.2°, 18.33°±0.2°, 19.75°±0.2°, and 22.61°±0.2°.

[0028] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows: Fig.10 shown.

[0029] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there is an endothermic signal peak accompanied by exothermic signal peak at 190-230°C, and the thermogravimetric analysis curve (TGA) shows that the sample loses 0.3% of weight during heating to 150°C, and decomposition may occur after 280°C, such as Fig. 9 shown.

[0030] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 14.62°±0.2°, 15.21°±0.2°, and 17.23°±0.2°.

[0031] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.89°±0.2°, 14.62°±0.2°, 15.21°±0.2°, 17.23°±0.2°, 18.33°±0.2°, 25.86°±0.2°.

[0032] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows: Fig.12 shown.

[0033] In a specific embodiment, the crystal form is a crystal form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 80-150°C, a melting endothermic peak at about 206°C, and a thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 0.3% during heating to 80°C and a weight loss of 2.8% during heating to 80-130°C. Decomposition may occur after 230°C, such as Fig.11 shown.

[0034] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and mandelic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.55°±0.2°, 7.98°±0.2°, 16.72°±0.2°, 18.43°±0.2°, 19.35°±0.2°, 19.83°±0.2°, and 21.87°±0.2°.

[0035] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and mandelic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.55°±0.2°, 5.93°±0.2°, 7.98°±0.2°, 16.72°±0.2°, 18.43°±0.2°, 19.35°±0.2°, 19.56°±0.2°, 19.83°±0.2°, 21.44°±0.2°, and 21.87°±0.2°.

[0036] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and mandelic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.14 shown.

[0037] In a specific embodiment, the crystal form is a crystal form A formed by the compound of formula (I) and mandelic acid, and its differential scanning calorimetry curve (DSC) shows endothermic signals corresponding to TGA weight loss at 80-120°C and 130-170°C, respectively. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 6.6% during heating to 120°C and a weight loss of 21.6% during heating to 120-220°C, which may correspond to the process of decomposition of mandelic acid eutectic and removal of mandelic acid, such as Fig.13 shown.

[0038] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and methanesulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.29°±0.2°, 16.97°±0.2°, 17.71°±0.2°, and 21.06°±0.2°.

[0039] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and methanesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.29°±0.2°, 8.68°±0.2°, 14.21°±0.2°, 16.18°±0.2°, 16.97°±0.2°, 17.71°±0.2°, 21.06°±0.2°, and 25.99°±0.2°.

[0040] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and methanesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.98°±0.2°, 5.29°±0.2°, 8.68°±0.2°, 10.15°±0.2°, 14.21°±0.2°, 16.18°±0.2°, 16.97°±0.2°, 17.27°±0.2°, 17.71°±0.2°, 19.60°±0.2°, 21.06°±0.2°, 22.98°±0.2°, and 25.99°±0.2°.

[0041] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.16 shown.

[0042] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows a signal peak of endothermic and exothermic at 160-210°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 0.8% of its weight during heating to 140°C, and may decompose after 270°C, such as Fig.15 shown.

[0043] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and methanesulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.57°±0.2°, 7.72°±0.2°, 11.09°±0.2°, and 22.20°±0.2°.

[0044] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.57°±0.2°, 7.72°±0.2°, 11.09°±0.2°, 16.10°±0.2°, 17.03°±0.2°, 19.19°±0.2°, 20.01°±0.2°, and 22.20°±0.2°.

[0045] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.57°±0.2°, 7.72°±0.2°, 8.07°±0.2°, 11.09°±0.2°, 16.10°±0.2°, 17.03°±0.2°, 19.19°±0.2°, 20.01°±0.2°, 20.57°±0.2°, 21.78°±0.2°, 22.20°±0.2°, 22.67°±0.2°, 24.24°±0.2°, 24.75°±0.2°, and 25.25°±0.2°.

[0046] In a specific embodiment, the crystalline form is the crystalline form B formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.18 shown.

[0047] In a specific embodiment, the crystalline form is the crystalline form B formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic signals accompanied by exothermic signals at 120-190°C, and the thermogravimetric analysis curve (TGA) shows that the sample loses 6.4% of its weight during heating to 140°C, and decomposition may occur after 280°C, such as Fig.17 shown.

[0048] In certain specific embodiments, the crystalline form is crystalline form C formed by the compound of formula (I) and methanesulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 4.57°±0.2°, 9.01°±0.2°, 9.18°±0.2°, and 17.48°±0.2°.

[0049] In certain specific embodiments, the crystalline form is crystalline form C formed by the compound of formula (I) and methanesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.57°±0.2°, 9.01°±0.2°, 9.18°±0.2°, 9.63°±0.2°, 9.84°±0.2°, 17.17°±0.2°, 17.48°±0.2°, and 20.26°±0.2°.

[0050] In certain specific embodiments, the crystalline form is crystalline form C formed by the compound of formula (I) and methanesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.57°±0.2°, 5.53°±0.2°, 9.01°±0.2°, 9.18°±0.2°, 9.63°±0.2°, 9.84°±0.2°, 17.17°±0.2°, 17.48°±0.2°, 19.00°±0.2°, 19.25°±0.2°, 19.81°±0.2°, 20.06°±0.2°, 20.26°±0.2°, 23.15°±0.2°, and 24.69°±0.2°.

[0051] In a specific embodiment, the crystalline form is a crystalline form C formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows: Fig. 20 shown.

[0052] In a specific embodiment, the crystalline form is the crystalline form C formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there is an endothermic signal peak accompanied by exothermic signal peak at 120-200°C, and the thermogravimetric analysis curve (TGA) shows that the sample loses 4.7% of its weight during heating to 160°C, and may decompose after 280°C, such as Fig.19 shown.

[0053] In certain specific embodiments, the crystalline form is crystalline form D formed by the compound of formula (I) and methanesulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.51°±0.2°, 11.07°±0.2°.

[0054] In a specific embodiment, the crystalline form is the crystalline form D formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig. 22 shown.

[0055] In a specific embodiment, the crystalline form is a crystalline form D formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 100-140°C, an endothermic signal at 140-160°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 8.7% of its weight during heating to 140°C, and decomposition may occur after 280°C, such as Fig.21 shown.

[0056] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.82°±0.2°, 16.43°±0.2°, 20.78°±0.2°, and 23.47°±0.2°.

[0057] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.63°±0.2°, 5.82°±0.2°, 16.43°±0.2°, 17.54°±0.2°, 18.43°±0.2°, 20.08°±0.2°, 20.78°±0.2°, and 23.47°±0.2°.

[0058] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.63°±0.2°, 5.82°±0.2°, 16.43°±0.2°, 17.54°±0.2°, 18.43°±0.2°, 20.08°±0.2°, 20.78°±0.2°, 23.47°±0.2°, 25.41°±0.2°, 25.70°±0.2°, and 25.82°±0.2°.

[0059] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.24 shown.

[0060] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and sulfuric acid, and its differential scanning calorimetry curve (DSC) shows that there is an endothermic signal peak accompanied by exothermicity at 170-210°C, and the thermogravimetric analysis curve (TGA) shows that the sample loses 1.7% of its weight during heating to 140°C, and decomposition may occur after 270°C, such as Fig.23 shown.

[0061] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.99°±0.2°, 14.45°±0.2°, 15.56°±0.2°, and 23.66°±0.2°.

[0062] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and sulfuric acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.99°±0.2°, 6.28°±0.2°, 7.30°±0.2°, 14.45°±0.2°, 15.56°±0.2°, 20.05°±0.2°, 20.98°±0.2°, and 23.66°±0.2°.

[0063] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and sulfuric acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.99°±0.2°, 6.28°±0.2°, 7.30°±0.2°, 12.43°±0.2°, 14.45°±0.2°, 15.56°±0.2°, 17.32°±0.2°, 17.69°±0.2°, 18.65°±0.2°, 20.05°±0.2°, 20.98°±0.2°, 21.58°±0.2°, 23.66°±0.2°, 25.68°±0.2°, and 29.84°±0.2°.

[0064] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.26 shown.

[0065] In a specific embodiment, the crystalline form is the crystalline form B formed by the compound of formula (I) and sulfuric acid, and its differential scanning calorimetry curve (DSC) shows that there is an endothermic signal peak accompanied by exothermic signal peak at 170-210°C, and the thermogravimetric analysis curve (TGA) shows that the sample loses 1.0% of its weight during heating to 120°C, and decomposition may occur after 280°C, such as Fig.25 shown.

[0066] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and hydrochloric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 8.27°±0.2°, 9.39°±0.2°, 15.61°±0.2°, 20.20°±0.2°.

[0067] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and hydrochloric acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 7.96°±0.2°, 8.27°±0.2°, 9.39°±0.2°, 15.61°±0.2°, 17.65°±0.2°, 20.20°±0.2°, 23.82°±0.2°, and 26.30°±0.2°.

[0068] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and hydrochloric acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 7.96°±0.2°, 8.27°±0.2°, 9.39°±0.2°, 10.58°±0.2°, 11.84°±0.2°, 15.61°±0.2°, 17.65°±0.2°, 18.88°±0.2°, 20.20°±0.2°, 22.55°±0.2°, 23.10°±0.2°, 23.82°±0.2°, 26.13°±0.2°, 26.30°±0.2°, and 26.87°±0.2°.

[0069] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and hydrochloric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.28 shown.

[0070] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and hydrochloric acid, and its differential scanning calorimetry (DSC) curve shows a broad endothermic signal corresponding to the first-order weight loss of TGA at 40-110°C, and an endothermic peak corresponding to the second-order weight loss of TGA at 120-170°C. The thermogravimetric analysis curve (TGA) shows that the sample has an 8.0% weight loss during heating to 100°C and a 5.7% weight loss during heating at 100-180°C, which may correspond to the process of decomposition of the hydrochloride and removal of hydrogen chloride, such as Fig. 27 shown.

[0071] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and hydrochloric acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 12.31°±0.2°, 17.95°±0.2°, 23.70°±0.2°, and 25.60°±0.2°.

[0072] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and hydrochloric acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.39°±0.2°, 3.80°±0.2°, 12.31°±0.2°, 12.82°±0.2°, 17.95°±0.2°, 23.70°±0.2°, 25.60°±0.2°, and 26.03°±0.2°.

[0073] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and hydrochloric acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.39°±0.2°, 3.80°±0.2°, 5.90°±0.2°, 10.25°±0.2°, 12.31°±0.2°, 12.82°±0.2°, 17.46°±0.2°, 17.95°±0.2°, 20.43°±0.2°, 21.52°±0.2°, 21.91°±0.2°, 22.63°±0.2°, 23.70°±0.2°, 25.60°±0.2°, and 26.03°±0.2°.

[0074] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and hydrochloric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.30 shown.

[0075] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and hydrochloric acid, and its differential scanning calorimetry curve (DSC) shows a broad endothermic signal corresponding to the first-order weight loss of TGA at 30-90°C, and an endothermic signal corresponding to the second-order weight loss of TGA at 110-160°C. The thermogravimetric analysis curve (TGA) shows that the sample has an 8.4% weight loss during heating to 90°C and a 14.1% weight loss during heating to 90°C, which may include the decomposition of the hydrochloride and the removal of hydrogen chloride, such as Fig.29 shown.

[0076] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and hydrobromic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 3.54°±0.2°, 4.83°±0.2°, 10.02°±0.2°, and 20.71°±0.2°.

[0077] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and hydrobromic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.54°±0.2°, 4.59°±0.2°, 4.83°±0.2°, 10.02°±0.2°, 14.39°±0.2°, 20.59°±0.2°, 20.71°±0.2°, and 22.49°±0.2°.

[0078] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and hydrobromic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.54°±0.2°, 4.59°±0.2°, 4.83°±0.2°, 10.02°±0.2°, 13.96°±0.2°, 14.39°±0.2°, 19.21°±0.2°, 19.52°±0.2°, 20.47°±0.2°, 20.59°±0.2°, 20.71°±0.2°, 22.49°±0.2°, 27.72°±0.2°, 27.82°±0.2°, and 28.13°±0.2°.

[0079] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and hydrobromic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.32 shown.

[0080] In a specific embodiment, the crystal form is a crystal form A formed by the compound of formula (I) and hydrobromic acid, and its differential scanning calorimetry (DSC) curve shows a broad endothermic signal corresponding to the first-order weight loss of TGA at 45-110°C, and an endothermic peak at 140-170°C. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 7.6% during heating to 100°C and a weight loss of 12.4% during heating to 100-200°C, which may correspond to the process of decomposition of hydrobromide and removal of hydrogen bromide, such as Fig.31 shown.

[0081] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and hydrobromic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 6.63°±0.2°, 22.18°±0.2°, 23.56°±0.2°, and 25.25°±0.2°.

[0082] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and hydrobromic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.63°±0.2°, 16.18°±0.2°, 22.18°±0.2°, 23.56°±0.2°, 25.25°±0.2°, 26.56°±0.2°, 26.96°±0.2°, and 28.13°±0.2°.

[0083] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and hydrobromic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.63°±0.2°, 16.18°±0.2°, 20.69°±0.2°, 21.87°±0.2°, 22.18°±0.2°, 23.56°±0.2°, 23.99°±0.2°, 24.38°±0.2°, 25.25°±0.2°, 26.56°±0.2°, 26.96°±0.2°, 28.13°±0.2°, 29.67°±0.2°, 31.30°±0.2°, and 31.57°±0.2°.

[0084] In a specific embodiment, the crystalline form is the crystalline form B formed by the compound of formula (I) and hydrobromic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows Fig.34 shown.

[0085] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and hydrobromic acid, and its differential scanning calorimetry (DSC) curve shows a broad endothermic signal corresponding to TGA weight loss at 70-180°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 5.5% during heating to 100°C and a weight loss of 17.1% during heating to 100-200°C, which may include the process of decomposition of hydrobromide and removal of hydrogen bromide, such as Fig.33 shown.

[0086] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and benzenesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.92°±0.2°, 6.65°±0.2°, 10.64°±0.2°, and 13.20°±0.2°.

[0087] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and benzenesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.60°±0.2°, 5.92°±0.2°, 6.65°±0.2°, 10.64°±0.2°, 11.80°±0.2°, 13.20°±0.2°, 20.18°±0.2°, and 20.53°±0.2°.

[0088] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and benzenesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.60°±0.2°, 5.92°±0.2°, 6.65°±0.2°, 10.64°±0.2°, 11.40°±0.2°, 11.80°±0.2°, 12.89°±0.2°, 13.20°±0.2°, 17.97°±0.2°, 20.18°±0.2°, 20.53°±0.2°, 20.65°±0.2°, 23.43°±0.2°, and 24.42°±0.2°.

[0089] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and benzenesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows: Fig.36 shown.

[0090] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and benzenesulfonic acid, and its differential scanning calorimetry (DSC) curve shows a broad endothermic signal corresponding to TGA weight loss at 30-100°C, and an endothermic signal peak accompanied by exothermic at 120-200°C. The thermogravimetric analysis curve (TGA) shows that the sample has a 2.5% weight loss during heating to 100°C, and a 1.3% weight loss during heating to 170°C. Decomposition may occur after 250°C, such as Fig.35 shown.

[0091] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and benzenesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.09°±0.2°, 7.28°±0.2°, 12.13°±0.2°, and 19.42°±0.2°.

[0092] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and benzenesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.09°±0.2°, 7.28°±0.2°, 10.89°±0.2°, 12.13°±0.2°, 12.43°±0.2°, 19.42°±0.2°, 20.36°±0.2°, and 21.79°±0.2°.

[0093] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and benzenesulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.02°±0.2°, 6.09°±0.2°, 7.28°±0.2°, 10.89°±0.2°, 12.13°±0.2°, 12.43°±0.2°, 15.83°±0.2°, 18.16°±0.2°, 19.42°±0.2°, 19.99°±0.2°, 20.36°±0.2°, 20.86°±0.2°, 21.08°±0.2°, 21.79°±0.2°, and 24.87°±0.2°.

[0094] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and benzenesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern is substantially as follows: Fig.38 shown.

[0095] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and benzenesulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows two corresponding TGA weight loss endothermic signal peaks at 30-150°C, and an exothermic signal peak at 160-200°C. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 2.1% during heating to 100°C, a weight loss of 5.1% during heating to 170°C, and a continuous weight loss after 250°C. Fig.37 shown.

[0096] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 9.10°±0.2°, 11.14°±0.2°, 18.70°±0.2°, and 21.43°±0.2°.

[0097] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 9.10°±0.2°, 11.14°±0.2°, 17.30°±0.2°, 18.70°±0.2°, 20.43°±0.2°, 21.43°±0.2°, 23.08°±0.2°, and 25.95°±0.2°.

[0098] In certain specific embodiments, the crystalline form is crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 9.10°±0.2°, 9.96°±0.2°, 11.14°±0.2°, 14.60°±0.2°, 15.89°±0.2°, 17.30°±0.2°, 18.70°±0.2°, 20.30°±0.2°, 20.43°±0.2°, 21.43°±0.2°, 21.79°±0.2°, 23.08°±0.2°, 24.67°±0.2°, 25.95°±0.2°, and 27.29°±0.2°.

[0099] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its X-ray powder diffraction pattern is substantially as follows using Cu-Kα radiation: Fig.40 shown.

[0100] In a specific embodiment, the crystalline form is a crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its differential scanning calorimetry (DSC) curve shows a broad endothermic signal corresponding to TGA weight loss at 50-120°C, an endothermic signal at around 282°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 2.3% of its weight during heating to 160°C, and may decompose after 290°C, such as Fig.39 shown.

[0101] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.43°±0.2°, 22.03°±0.2°, 22.42°±0.2°, and 22.92°±0.2°.

[0102] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 7.43°±0.2°, 9.86°±0.2°, 17.81°±0.2°, 19.27°±0.2°, 20.80°±0.2°, 22.03°±0.2°, 22.42°±0.2°, and 22.92°±0.2°.

[0103] In certain specific embodiments, the crystalline form is crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.65°±0.2°, 7.43°±0.2°, 9.86°±0.2°, 11.59°±0.2°, 15.67°±0.2°, 17.21°±0.2°, 17.81°±0.2°, 18.06°±0.2°, 19.27°±0.2°, 20.80°±0.2°, 22.03°±0.2°, 22.42°±0.2°, 22.92°±0.2°, 25.90°±0.2°, and 26.79°±0.2°.

[0104] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its X-ray powder diffraction pattern is substantially as follows using Cu-Kα radiation: Fig.42 shown.

[0105] In a specific embodiment, the crystalline form is a crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its differential scanning calorimetry curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 25-120°C, an exothermic signal at 241°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 7.5% of its weight during heating to 130°C, and decomposition may occur after 280°C, such as Fig.41 shown.

[0106] In certain specific embodiments, the crystalline form is crystalline form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its X-ray powder diffraction pattern using Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 6.62°±0.2°, 6.77°±0.2°, 6.87°±0.2°, and 9.71°±0.2°.

[0107] In certain specific embodiments, the crystalline form is a crystalline form C formed by a compound of formula (I) and 1,5-naphthalene disulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.62°±0.2°, 6.77°±0.2°, 6.87°±0.2°, 7.22°±0.2°, 9.57°±0.2°, 9.71°±0.2°, 19.58°±0.2°, 19.77°±0.2°

[0108] In certain specific embodiments, the crystalline form is crystalline form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, wherein, using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.58°±0.2°, 6.62°±0.2°, 6.77°±0.2°, 6.87°±0.2°, 7.22°±0.2°, 7.39°±0.2°, 9.57°±0.2°, 9.71°±0.2°, 10.13°±0.2°, 16.18°±0.2°, 18.67°±0.2°, 19.58°±0.2°, 19.77°±0.2°, and 21.93°±0.2°.

[0109] In a specific embodiment, the crystalline form is a crystalline form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its X-ray powder diffraction pattern is substantially as follows using Cu-Kα radiation: Fig.44 shown.

[0110] In a specific embodiment, the crystalline form is a crystalline form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its differential scanning calorimetry (DSC) curve shows a broad endothermic signal corresponding to TGA weight loss at 40-110°C, an endothermic signal at 230-260°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 10.3% of its weight during heating to 110°C, and may decompose after 280°C, such as Fig.43 shown.

[0111] The present invention also provides a pharmaceutical composition, wherein the pharmaceutical composition contains a therapeutically effective amount of any of the aforementioned crystalline forms and a pharmaceutically acceptable carrier and / or excipient, preferably the therapeutically effective amount is 1-1500 mg. The pharmaceutical composition may be in the form of a unit preparation (a unit preparation is also referred to as a "preparation specification").

[0112] The present invention also provides use of the crystal form or composition described in any one of the above schemes in the preparation of a drug for treating tumor diseases associated with USP1. Furthermore, the disease mediated by USP1 is a tumor.

[0113] The present invention also provides a method for treating a tumor disease associated with USP1, the method comprising administering to a subject a therapeutically effective amount of the crystalline form or a composition thereof as shown in any one of the aforementioned schemes, the disease is preferably a tumor, and the therapeutically effective amount is preferably 1-1500 mg. In some embodiments, the mammal in the present invention includes a human.

[0114] "Effective amount" or "therapeutically effective amount" as used herein refers to administering a sufficient amount of the crystalline forms disclosed herein that will alleviate one or more symptoms of the disease or condition being treated to some extent. In some embodiments, the result is a reduction and / or alleviation of the signs, symptoms or causes of the disease, or any other desired change in the biological system. For example, an "effective amount" for therapeutic use is the amount of a composition comprising the crystalline forms disclosed herein that is required to provide a clinically significant reduction in disease symptoms. Examples of therapeutically effective amounts include, but are not limited to, 1-1500 mg, 1-1400 mg, 1-1300 mg, 1-1200 mg, 1-1000 mg, 1-900 mg, 1-800 mg, 1-700 mg, 1-600 mg, 1-500 mg, 1-400 mg, 1-300 mg, 1-250 mg, 1-200 mg, 1-150 mg, 1-125 mg, 1-100 mg, 1-80 mg, 1-60 mg, 1-50 mg, 1-40 mg, 1-25 mg, 1- 20mg, 5-1500mg, 5-1000mg, 5-900mg, 5-800mg, 5-700mg, 5-600mg, 5-500mg, 5-400mg, 5-300mg, 5-250mg, 5-200mg, 5 -150mg, 5-125mg, 5-100mg, 5-90mg, 5-70mg, 5-80mg, 5-60mg, 5-50mg, 5-40mg, 5-30mg, 5-25mg, 5-20mg, 10-1500mg, 10-1000mg, 10-900mg, 10-800mg, 10-700mg, 10-600mg, 10-500mg, 10-450mg, 10-400mg, 10-300mg, 10-250mg, 10-20 0mg, 10-150mg, 10-125mg, 10-100mg, 10-90mg, 10-80mg, 10-70mg, 10-60mg, 10-50mg, 10-40mg, 10-30mg, 10-20mg; 2 0-1500mg, 20-1000mg, 20-900mg, 20-800mg, 20-700mg, 20-600mg, 20-500mg, 20-400mg, 20-350mg, 20-300mg, 20-25 0mg, 20-200mg, 20-150mg, 20-125mg, 20-100mg, 20-90mg, 20-80mg, 20-70mg, 20-60mg, 20-50mg, 20-40mg, 20-30mg;50-1500mg, 50-1000mg, 50-900mg, 50-800mg, 50-700mg, 50-600mg, 50-500mg, 50-400mg, 50-300mg, 50-250mg, 50-200mg, 50-150mg, 50-125mg, 5 0-100mg; 100-1500mg, 100-1000mg, 100-900mg, 100-800mg, 100-700mg, 100-600mg, 100-500mg, 100-400mg, 100-300mg, 100-250mg, 100-200mg;

[0115] In some embodiments, the pharmaceutical composition or preparation of the present invention contains the above-mentioned therapeutically effective amount of the crystalline form of the present invention;

[0116] The present invention relates to a pharmaceutical composition or pharmaceutical preparation, which comprises a therapeutically effective amount of the crystalline form of the present invention and a carrier and / or excipient. The pharmaceutical composition can be in the form of a unit preparation (the amount of the main drug in the unit preparation is also referred to as a "preparation specification"). In some embodiments, the pharmaceutical composition includes but is not limited to 1 mg, 1.25 mg, 2.5 mg, 5 mg, 10 mg, 12.5 mg, 15 mg, 20 mg, 25 mg, 30 mg, 35 mg, 40 mg, 45 mg, 50 mg, 55 mg, 60 mg, 65 mg, 70 mg, 75 mg, 80 mg, 85 mg, 90 mg, 95 mg, 100 mg, 110 mg, 120 mg, 125 mg, 130 mg, 140 mg, 150 mg, 160 mg, 170 mg, 180 mg, 190 mg, 200 mg, 210 mg, 220 1500mg, 1000mg, 1100mg, 1200mg, 1300mg, 1400mg and 1500mg of the crystalline form of the present invention.

[0117] A method for treating a disease in a mammal, the method comprising administering to a subject a therapeutically effective amount of the crystalline form of the present invention, and a pharmaceutically acceptable carrier and / or excipient, the therapeutically effective amount is preferably 1-1500 mg, and the disease is preferably a tumor, especially a solid tumor.

[0118] A method for treating a disease in a mammal, the method comprising administering the drug crystal form of the present invention, and a pharmaceutically acceptable carrier and / or excipient to a subject at a daily dose of 1-1500 mg / day, the daily dose may be a single dose or divided doses, in some embodiments, the daily dose includes but is not limited to 10-1500 mg / day, 20-1500 mg / day, 25-1500 mg / day, 50-1500 mg / day, 75-1500 mg / day, 100-1500 mg / day, 200-1500 mg / day, 10-1000 mg / day, 20-1000 mg / day, 25-1000 mg / day, 50-1000 mg / day, 75-1000 mg / day, 100-1000 mg / day. In some embodiments, the daily dose includes but is not limited to 1 mg / day, 5 mg / day, 10 mg / day, 20 mg / day, 25 mg / day, 50 mg / day, 50 mg / day, 75 mg / day, 100 mg / day, 125 mg / day, 150 mg / day, 200 mg / day, 400 mg / day, 600 mg / day, 800 mg / day, 1000 mg / day, 1200 mg / day, 1400 mg / day, 1500 mg / day.

[0119] The present invention relates to a kit, which may include a crystal form in a single-dose or multi-dose form. The kit contains the crystal form of the present invention, and the amount of the crystal form of the present invention is the same as that in the above-mentioned pharmaceutical composition.

[0120] The amounts of the crystalline forms according to the invention in the present invention are in each case calculated as the free base.

[0121] "Preparation specifications" refers to the weight of the main drug contained in each vial, tablet or other unit preparation.

[0122] The crystalline form of the present invention is present in an amount of about 5% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 10% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 15% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 20% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 25% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 30% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 35% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 40% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 45% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 50% to about 100% by weight of the drug substance; in certain embodiments, it is present in an amount of about 55% to about 100% by weight of the drug substance. In some embodiments, the drug substance is present in an amount of about 60% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 65% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 70% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 75% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 80% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 85% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 90% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 95% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 98% to about 100% by weight of the drug substance; in some embodiments, the drug substance is present in an amount of about 99% to about 100% by weight of the drug substance; in some embodiments, substantially all of the drug substance is substantially pure crystals.

[0123] The crystalline form of the present invention can be prepared by the following preparation method:

[0124] 1. Volatilization experiment: Add the compound of formula I into a selected single solvent or binary solvent to form a clear sample solution, and evaporate it open at different temperatures until the solvent is dry.

[0125] 2. Suspension method: Add the compound of formula I to a selected single solvent or binary solvent until a suspension is formed. After suspending and stirring at room temperature to 50°C for a certain period of time (e.g., 1h to 3 days, or 2h to 24h, or 2h to 12h, or 3 to 5h), the suspension is centrifuged and dried to obtain the product.

[0126] 3. Dissolution crystallization method: dissolve the compound of formula I in a good solvent, add a certain amount of the solution dropwise to a poor solvent or add a poor solvent dropwise to the solution, stir to precipitate a solid, separate and dry to obtain the solid.

[0127] 4. Cooling method: dissolve a certain amount of sample into the corresponding solvent at high temperature, transfer the solution to room temperature for cooling, let it stand or stir for crystallization, separate, and dry.

[0128] 5. Thermal method experiment: Take a certain amount of sample, place it on a glass slide and put it on a hot table, heat it to the target temperature at a certain rate (such as 5-20℃ / min, or 10-15℃ / min), and keep it at a constant temperature for a period of time (such as 0.5-5min, or 1-3min, or 1-2min), and then cool it naturally to room temperature to obtain a solid.

[0129] 6. Gas phase diffusion experiment: add a certain amount of compound of formula I to a proper amount of good solvent at room temperature to completely dissolve the sample or prepare a saturated solution of the good solvent; take a certain amount of solution, place the clear solution in a poor solvent atmosphere at room temperature until solid precipitates, separate, and obtain. Alternatively, directly place the solid compound of formula I in a solvent atmosphere and let it stand at room temperature for 1 to 7 days to obtain.

[0130] The good solvent and the poor solvent described in the present invention are relative. In a pair of solvents, the one with higher solubility is the good solvent, and the one with lower solubility is the poor solvent. The solvent used in the above preparation method can be a single solvent or a combination of two or more solvents when not specified.

[0131] The X-ray powder diffraction or DSC graph, TGA graph disclosed in the present invention and those substantially the same also belong to the scope of the present invention.

[0132] Unless otherwise stated, the terms used in the specification and claims have the following meanings:

[0133] “IC 50 ” refers to the half inhibitory concentration, which refers to the concentration at which half of the maximum inhibitory effect is achieved.

[0134] As used in the present invention, "the crystal of the present invention", "the crystal form of the present invention", "the crystal form of the present invention" and the like can be used interchangeably.

[0135] The crystal form of the present invention refers to the crystal form of the salt or co-crystal formed by the compound of formula (I) and the corresponding acid.

[0136] The "room temperature" mentioned in the present invention generally refers to 4-30°C, preferably refers to 20±5°C.

[0137] The crystalline structure of the present invention can be analyzed using various analytical techniques known to those of ordinary skill in the art, including but not limited to, X-ray powder diffraction (XRD), differential scanning calorimetry (DSC) and / or thermogravimetric analysis (TGA), also known as thermogravimetry (TG).

[0138] The "2θ or 2θ angle" described in the present invention refers to the peak position expressed in degrees (°) based on the setting in the X-ray diffraction experiment, and is usually the horizontal coordinate unit in the diffraction pattern. If the reflection is diffracted when the incident beam forms an angle θ with a certain lattice plane, the experimental setting needs to record the reflected beam at an angle of 2θ. It should be understood that the specific 2θ value of a specific crystal form mentioned in this article is intended to represent the 2θ value (expressed in degrees) measured using the X-ray diffraction experimental conditions described herein, and the error range of 2θ may be ±0.3, ±0.2 or ±0.1.

[0139] It is understood that the numerical values ​​described and protected by the present invention are approximate values. The variation in the numerical values ​​may be due to the calibration of the equipment, equipment error, purity of the crystal, crystal size, sample size and other factors.

[0140] It is to be understood that the crystal forms of the present invention are not limited to characteristic spectra that are completely identical to the characteristic spectra described in the accompanying drawings disclosed in the present invention, such as XRD, DSC, TGA, and DVS. Any crystal forms having characteristic spectra that are substantially the same or essentially the same as those described in the accompanying drawings fall within the scope of the present invention.

[0141] It is understood that, as is well known in the field of differential scanning calorimetry (DSC), the melting peak height of a DSC curve depends on many factors related to sample preparation and instrument geometry, while the peak position is relatively insensitive to experimental details. Therefore, in some embodiments, the crystalline compound of the present invention is characterized by a DSC graph having a characteristic peak position, having substantially the same properties as the DSC graph provided in the accompanying drawings of the present invention, and the measurement value error tolerance is within ±5°C, generally required to be within ±3°C.

[0142] "Carrier" refers to a system that does not cause significant irritation to the organism and does not eliminate the biological activity and properties of the administered compound, and can change the way the drug enters the human body and its distribution in the body, control the release rate of the drug and deliver the drug to the targeted organ. Non-limiting examples include microcapsules and microspheres, nanoparticles, liposomes, etc.

[0143] "Excipient" refers to a substance that is not a therapeutic agent in itself but is used as a diluent, adjuvant, binder and / or vehicle that is added to a pharmaceutical composition to improve its handling or storage properties or to allow or facilitate the formation of a compound or pharmaceutical composition into a unit dosage form for administration. As known to those skilled in the art, pharmaceutical excipients can serve a variety of functions and can be described as wetting agents, buffers, suspending agents, lubricants, emulsifiers, disintegrants, absorbents, preservatives, surfactants, colorants, flavoring agents and sweeteners. Examples of pharmaceutical excipients include, but are not limited to: (1) sugars such as lactose, glucose and sucrose; (2) starches such as corn starch and potato starch; (3) cellulose and its derivatives such as sodium carboxymethylcellulose, ethylcellulose, cellulose acetate, hydroxypropyl methylcellulose, hydroxypropyl cellulose, microcrystalline cellulose and cross-linked carboxymethylcellulose (e.g., cross-linked sodium carboxymethylcellulose); (4) tragacanth powder; (5) malt; (6) gelatin; (7) talc; (8) excipients such as cocoa butter and suppository waxes; (9) oils, such as peanut oil, cottonseed oil, safflower oil, sesame oil, olive oil, corn oil and soybean oil; (10) glycols, such as propylene glycol; (11) polyols, such as glycerol, sorbitol, mannitol and polyethylene glycol; (12) esters, such as ethyl oleate and ethyl laurate; (13) agar; (14) buffers, such as magnesium hydroxide and aluminum hydroxide; (15) alginic acid; (16) pyrogen-free water; (17) isotonic saline; (18) Ringer's solution; (19) ethanol; (20) pH buffer solutions; (21) polyesters, polycarbonates and / or polyanhydrides; and (22) other nontoxic compatible substances used in pharmaceutical preparations. BRIEF DESCRIPTION OF THE DRAWINGS

[0144] Figure 1 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0145] Figure 2 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0146] Figure 3 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0147] Figure 4 The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0148] Figure 5 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form C formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0149] Figure 6 The X-ray powder diffraction pattern of the crystalline form C formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0150] Figure 7 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and benzoic acid.

[0151] Figure 8 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and benzoic acid.

[0152] Fig. 9 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and D(+)-10-camphorsulfonic acid.

[0153] Fig.10 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and D(+)-10-camphorsulfonic acid.

[0154] Fig.11 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and 3,5-dihydroxybenzoic acid.

[0155] Fig.12 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and 3,5-dihydroxybenzoic acid.

[0156] Fig.13 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and mandelic acid.

[0157] Fig.14 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and mandelic acid.

[0158] Fig.15 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and methanesulfonic acid.

[0159] Fig.16 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and methanesulfonic acid.

[0160] Fig.17 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and methanesulfonic acid.

[0161] Fig.18The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and methanesulfonic acid.

[0162] Fig.19 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form C formed by the compound represented by formula (I) and methanesulfonic acid.

[0163] Fig. 20 The X-ray powder diffraction pattern of the crystalline form C formed by the compound represented by formula (I) and methanesulfonic acid.

[0164] Fig.21 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form D formed by the compound represented by formula (I) and methanesulfonic acid.

[0165] Fig. 22 The X-ray powder diffraction pattern of the crystalline form D formed by the compound represented by formula (I) and methanesulfonic acid.

[0166] Fig.23 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and sulfuric acid.

[0167] Fig.24 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and sulfuric acid.

[0168] Fig.25 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and sulfuric acid.

[0169] Fig.26 The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and sulfuric acid.

[0170] Fig. 27 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and hydrochloric acid.

[0171] Fig.28 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and hydrochloric acid.

[0172] Fig.29 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and hydrochloric acid.

[0173] Fig.30 The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and hydrochloric acid.

[0174] Fig.31The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and hydrobromic acid.

[0175] Fig.32 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and hydrobromic acid.

[0176] Fig.33 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and hydrobromic acid.

[0177] Fig.34 The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and hydrobromic acid.

[0178] Fig.35 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and benzenesulfonic acid.

[0179] Fig.36 The X-ray powder diffraction spectrum of the crystalline form A formed by the compound represented by formula (I) and benzenesulfonic acid.

[0180] Fig.37 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and benzenesulfonic acid.

[0181] Fig.38 The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and benzenesulfonic acid.

[0182] Fig.39 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form A formed by the compound represented by formula (I) and 1,5-naphthalene disulfonic acid.

[0183] Fig.40 The X-ray powder diffraction pattern of the crystalline form A formed by the compound represented by formula (I) and 1,5-naphthalene disulfonic acid.

[0184] Fig.41 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form B formed by the compound represented by formula (I) and 1,5-naphthalene disulfonic acid.

[0185] Fig.42 The X-ray powder diffraction pattern of the crystalline form B formed by the compound represented by formula (I) and 1,5-naphthalene disulfonic acid.

[0186] Fig.43 The differential scanning calorimetry analysis curve and thermogravimetric analysis spectrum of the crystalline form C formed by the compound represented by formula (I) and 1,5-naphthalene disulfonic acid.

[0187] Fig.44 The X-ray powder diffraction pattern of the crystalline form C formed by the compound represented by formula (I) and 1,5-naphthalene disulfonic acid.

[0188] Fig.45 The XRPD characterization diagram of the crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid under different conditions such as high temperature (60°C).

[0189] Fig.46 The XRPD characterization diagram of the crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid under different conditions such as high temperature (60° C.).

[0190] Fig.47 The XRPD characterization diagram of the crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid under different conditions such as high temperature (60°C).

[0191] Fig.48 The XRPD characterization diagram of the crystalline form B formed by the compound of formula (I) and sulfuric acid under different conditions such as high temperature (60°C). DETAILED DESCRIPTION

[0192] The structures of the compounds were determined by nuclear magnetic resonance (NMR) or / and mass spectrometry (MS). NMR shifts (δ) were measured in 10 -6 The unit of (ppm) is given. NMR measurements were performed using a Bruker Avance III 400 and Bruker Avance 300 nuclear magnetic spectrometer, with deuterated dimethyl sulfoxide (DMSO-d6), deuterated chloroform (CDCl3), deuterated methanol (CD3OD) as the measuring solvent, and tetramethylsilane (TMS) as the internal standard.

[0193] MS was measured using (Agilent 6120B (ESI) and Agilent 6120B (APCI)).

[0194] HPLC measurement was performed using LC-20AT (Shimadzu) high pressure liquid chromatograph (Shim-pack GIST C18, 4.6×250 mm (HSS), 5 μm).

[0195] XRD was analyzed using an X-ray powder diffractometer, Bruker D8 Advance Diffractometer. The 2θ scanning angle was from 3° to 45°, the scanning step was 0.013°, and the exposure time was 0.08 seconds. When testing the sample, the tube voltage and current were 45 kV and 40 mA, respectively, and the sample pan was a zero background sample pan.

[0196] TGA test conditions: The model of the thermogravimetric analyzer is TA Discovery 550 (TA, US). 2-5 mg of sample was placed in a balanced sample pan and automatically weighed in the TGA heating furnace. The sample was heated to the final temperature at a rate of 10 ° C / min, and the nitrogen purge rate at the sample was 60 mL / min, and the nitrogen purge rate at the balance was 40 mL / min.

[0197] DSC test conditions: The model of differential scanning calorimeter is TA Discovery 250 (TA, US). 1-2 mg of sample is accurately weighed and placed in a standard pan or a perforated DSC Tzero sample pan, and heated to the final temperature at a rate of 10°C / min, and the nitrogen purge rate in the furnace is 50 mL / min.

[0198] The known starting materials of the present invention can be synthesized by methods known in the art, or can be purchased from companies such as Titan Technology, Anage Chemical, Shanghai Demo, Chengdu Kelon Chemical, Shaoyuan Chemical Technology, and Bailingwei Technology.

[0199] Unless otherwise specified in the examples, the solution refers to an aqueous solution.

[0200] Unless otherwise specified in the examples, the room temperature is 20°C to 30°C.

[0201] The implementation process of the present invention and the beneficial effects produced are described in detail below through specific embodiments, which is intended to help readers better understand the essence and characteristics of the present invention, and is not intended to limit the scope of implementation of the present invention.

[0202] Example 1: Preparation of the compound of formula (I)

[0203]

[0204] Step 1: Preparation of 2A

[0205] 4-(Methoxycarbonyl)bicyclo[2.2.2]octane-1-carboxylic acid (5 g, 23.58 mmol) was dissolved in THF (60 mL), and borane tetrahydrofuran solution (47 mL, 1 M) was slowly added dropwise at 0°C, and stirred at room temperature overnight. Methanol was added at 0°C to quench the mixture, and the mixture was concentrated under reduced pressure. The residue was purified by silica gel column chromatography (ethyl acetate / petroleum ether (V / V) = 1 / 20-1 / 2) to obtain 2A (3.8 g, yield: 81%).

[0206] LCMS m / z=199.2[M+H] +

[0207] Step 2: Preparation of 2B

[0208] 2A (3.8 g, 19.16 mmol) was dissolved in DCM (100 mL), and Dess-Martin periodinane (16.25 g, 38.32 mmol) was added in batches at 0°C, and the mixture was reacted at room temperature for 3 h. The reaction was completed by TLC monitoring, and the mixture was concentrated under reduced pressure. The residue was purified by silica gel column chromatography (ethyl acetate / petroleum ether (V / V) = 1 / 20-1 / 2) to obtain 2B (3.02 g, yield: 80%).

[0209] LCMS m / z=197.1[M+H] +

[0210] Step 3: Preparation of 2C

[0211] 1,1-Dibromo-3,3,3-trifluoroacetone (4.98 g, 18.49 mmol, CAS: 431-67-4) was placed in a 250 mL single-mouth bottle, 30 mL of water and sodium acetate (1.89 g, 23.09 mmol) were added, and the mixture was reacted at 90°C for 1 h. After cooling to room temperature, 60 mL of methanol, 2B (3.02 g, 15.39 mmol) and concentrated aqueous ammonia (15 mL) were added in sequence, and the mixture was reacted at 90°C for 2 h. After cooling to room temperature, the reaction solution was poured into 200 mL of water, filtered, and the filter cake was washed with water (2 x 10 mL), and the filter cake was dried under reduced pressure to obtain 2C (2.9 g, yield: 62%).

[0212] LCMS m / z=303.1[M+H] +

[0213] 1 H NMR (400MHz, DMSO-d6) δ12.36–12.16(m,1H),7.68–7.55(m,1H),3.59(s,3H),1.90-1.72(m,12H).

[0214] Step 4: 2D preparation

[0215] 2C (2.0 g, 6.62 mmol) was dissolved in 30 mL DMF at room temperature, and isopropyl iodide (4.50 g, 26.48 mmol) and cesium carbonate (6.47 g, 19.86 mmol) were added in sequence, and the mixture was reacted at 90°C overnight. After cooling to room temperature, water and ethyl acetate were added for extraction, and the organic layer was washed with saturated brine, dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The residue was purified by silica gel column chromatography (ethyl acetate / petroleum ether (V / V) = 1 / 20-1 / 1) to obtain 2D (1.2 g, yield: 52%).

[0216] LCMS m / z=345.2[M+H] +

[0217] Step 5: Preparation of 2E

[0218] 2D (1.2 g, 3.48 mmol) was dissolved in 20 mL THF, lithium borohydride (0.38 g, 17.40 mmol) was added, and the mixture was stirred at 60°C for 2 h. After cooling to room temperature, a saturated aqueous solution of ammonium chloride was added to quench the reaction, and water and ethyl acetate were added for extraction. The organic layer was dried over anhydrous sodium sulfate and concentrated under reduced pressure to obtain 2E (0.9 g, yield: 81%).

[0219] LCMS m / z=317.2[M+H] +

[0220] Step 6: Preparation of 2F

[0221] At 0°C, methylsulfonyl chloride (64 mg, 0.56 mmol) was added to a solution of 2E (0.12 g, 0.37 mmol) and triethylamine (0.11 g, 1.09 mmol) in dichloromethane (15 mL), and stirred at room temperature for 1 h. 20 mL of saturated sodium bicarbonate aqueous solution was added to quench, and dichloromethane (20 mL × 3) was used for extraction. The organic phases were combined, dried over anhydrous sodium sulfate, concentrated under reduced pressure, and purified by silica gel column chromatography (ethyl acetate / petroleum ether (V / V) = 1 / 100-1 / 20) to obtain 2F (0.11 g, yield 74%).

[0222] LCMS m / z=395.1[M+H] +

[0223] Step 7: Preparation of 2G

[0224] 1F (0.1 g, 0.58 mmol) and 2F (0.23 g, 0.58 mmol) were dissolved in DMF (5 mL), cesium carbonate (0.38 g, 1.17 mmol) and sodium iodide (0.087 g, 0.58 mmol) were added, and the mixture was reacted at 140°C for 2 h. After cooling to room temperature, 20 mL of water and 20 mL of ethyl acetate were added for extraction, and the organic layer was washed with saturated brine (10 mL x 3), dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The residue was purified by silica gel column chromatography (ethyl acetate / petroleum ether (V / V) = 1 / 10-1 / 2) to obtain 2G (0.060 g, yield: 22%).

[0225] LCMS m / z=470.2[M+H] +

[0226] Step 8: Preparation of the compound of formula (I)

[0227] 2G (0.06 g, 0.13 mmol), (4-cyclopropyl-6-methoxypyrimidin-5-yl)boric acid (0.050 g, 0.26 mmol), XPhos G3 (0.011 g, 0.013 mmol, CAS: 1445085-55-1) and potassium phosphate (0.056 g, 0.27 mmol) were placed in a 50 mL single-necked bottle, 1,4-dioxane (4 mL) and water (1 mL) were added, the atmosphere was replaced with nitrogen three times, the temperature was raised to 90 °C and stirred overnight. The mixture was cooled to room temperature, and 20 mL of water and 20 mL of ethyl acetate were added for extraction. The organic layer was dried over anhydrous sodium sulfate and concentrated under reduced pressure. The residue was purified by silica gel column chromatography (ethyl acetate / petroleum ether (V / V) = 1 / 10-1 / 1). After concentration, the residue was purified by secondary silica gel column chromatography (dichloromethane / methanol (V / V) = 100 / 0-100 / 3) to obtain the compound of formula (I) (30 mg, yield: 39%).

[0228] LCMS m / z=584.2[M+H] +

[0229] 1 H NMR(400MHz,CD3OD)δ8.97(d,1H),8.64(s,1H),8.38(d,1H),7.65–7.58(m,1H),4.93–4.84(m,1H),4.39(s,2H),3.93 (s,3H),2.06–1.94(m,6H),1.74–1.59(m,7H),1.41(d,6H),1.27–1.20(m,1H),1.16–1.09(m,1H),0.99–0.86(m,2H).

[0230] Preparation of co-crystals or crystalline forms of salts

[0231] Example 2: Preparation of Crystalline Form A Formed by the Compound of Formula (I) and p-Hydroxybenzoic Acid

[0232] About 29.2 mg of the compound represented by formula (I) and 7.6 mg of p-hydroxybenzoic acid were added to 2 ml of n-heptane, and stirred at room temperature for 1 day. The suspension was centrifuged and the solid was vacuum dried at room temperature to obtain a crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid.

[0233] Example 3: Preparation of Crystalline Form B Formed by Compound of Formula (I) and p-Hydroxybenzoic Acid

[0234] Take 29.2 mg of the compound represented by formula (I) and 7.6 mg of p-hydroxybenzoic acid, add them to 2.0 mL of acetone, suspend and stir to completely dissolve the sample, and let the clear solution stand in the open at room temperature until the solvent is completely evaporated to obtain a solid crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid.

[0235] Example 4: Preparation of Crystalline Form C Formed by the Compound of Formula (I) and p-Hydroxybenzoic Acid

[0236] Take 29.2 mg of the compound represented by formula (I) and 7.6 mg of p-hydroxybenzoic acid, add them into 2.0 mL of tetrahydrofuran, suspend and stir to completely dissolve the sample, and let the clear solution stand at room temperature in an open air until the solvent is completely evaporated to obtain a solid, thereby obtaining a crystalline form C formed by the compound represented by formula (I) and p-hydroxybenzoic acid.

[0237] Example 5: Preparation of Crystalline Form A Formed by Compound of Formula (I) and Benzoic Acid

[0238] About 29.2 mg of the compound represented by formula (I) and 6.7 mg of benzoic acid were added to 2 ml of n-heptane, and stirred at room temperature for 1 day. The suspension was centrifuged and the solid was vacuum dried at room temperature to obtain a crystalline form A formed by the compound represented by formula (I) and benzoic acid.

[0239] Example 6: Preparation of Crystalline Form A Formed by the Compound of Formula (I) and D(+)-10-Camphorsulfonic Acid

[0240] About 29.2 mg of the compound represented by formula (I) and 12.8 mg of D-10-camphorsulfonic acid were added to 1 ml of isopropyl ether / ethanol (v / v=3:1), and stirred at room temperature for 1 day. The suspension was centrifuged and the solid was vacuum dried at room temperature to obtain a crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid.

[0241] Example 7: Preparation of Crystalline Form A Formed by the Compound of Formula (I) and 3,5-Dihydroxybenzoic Acid

[0242] Take 29.2 mg of the compound represented by formula (I) and 8.5 mg of 3,5-dihydroxybenzoic acid, add them to 2.0 mL of acetone, suspend and stir to completely dissolve the sample, cool the clear solution to -15°C, take 0.3 ml of the solution, add 3 ml of n-heptane to obtain a solid, and obtain a crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid.

[0243] Example 8: Preparation of Crystalline Form A Formed by the Compound of Formula (I) and Mandelic Acid

[0244] Take 29.2 mg of the compound represented by formula (I) and 8.4 mg of mandelic acid, add them to 2.0 mL of tetrahydrofuran, suspend and stir to completely dissolve the sample, cool the clear solution to -15°C, take 0.3 ml of the solution, add 3 ml of n-heptane to obtain a solid, and obtain crystalline form A formed by the compound of formula (I) and mandelic acid.

[0245] Example 9: Preparation of Crystalline Form A Formed by Compound of Formula (I) and Methanesulfonic Acid

[0246] Take about 29.2 mg of the compound represented by formula (I) and 55.0 μL of methanesulfonic acid, add them to 2 ml of n-heptane, stir at room temperature for 1 day, centrifuge the suspension, and vacuum dry the solid at room temperature to obtain the crystalline form A formed by the compound represented by formula (I) and methanesulfonic acid.

[0247] Example 10: Preparation of Crystalline Form B of the Compound of Formula (I) and Methanesulfonic Acid

[0248] Take about 29.2 mg of the compound represented by formula (I) and 55.0 μL of methanesulfonic acid, add them to 2 ml of isopropyl ether / ethanol (v / v=3:1), stir at room temperature for 1 day, centrifuge the suspension, and vacuum dry the solid at room temperature to obtain the crystalline form B formed by the compound of formula (I) and methanesulfonic acid.

[0249] Example 11: Preparation of Crystalline Form C of the Compound of Formula (I) and Methanesulfonic Acid

[0250] Take 29.2 mg of the compound represented by formula (I) and 55.0 μL of methanesulfonic acid, add them to 2.0 mL of acetone, suspend and stir to completely dissolve the sample, and let the clear solution stand in the open air at room temperature until the solvent is completely evaporated to obtain solid methanesulfonic acid crystal form C of the compound represented by formula (I).

[0251] Example 12: Preparation of Crystalline Form A of the Compound of Formula (I) and Sulfuric Acid

[0252] Take about 29.2 mg of the compound represented by formula (I) and 55.0 μL of sulfuric acid, add them to 2 ml of n-heptane, stir at room temperature for 1 day, centrifuge the suspension, and vacuum dry the solid at room temperature to obtain the crystalline form A formed by the compound represented by formula (I) and sulfuric acid.

[0253] Example 13: Preparation of Crystalline Form B of the Compound of Formula (I) and Sulfuric Acid

[0254] 1168.2 mg of the compound represented by formula (I) was added to 40 mL of isopropyl ether / ethanol (v / v, 3:1) and suspended and stirred. 2.2 mL of ethanolic sulfuric acid solution (1M) was added. After suspending and stirring for 4 days, the suspension was centrifuged and the solid was vacuum dried overnight at room temperature for characterization. The obtained sample was added to the mother liquor and 0.7 mL of ethanolic sulfuric acid solution (1M) was added. After suspending and stirring for 2 days, the suspension was centrifuged and the solid was vacuum dried overnight at room temperature. Crystal form B formed by the compound of formula (I) and sulfuric acid was obtained.

[0255] Example 14: Preparation of Crystalline Form A Formed by Compound of Formula (I) and Hydrochloric Acid

[0256] 29.2 mg of the compound represented by formula (I) and 55.0 μL of hydrochloric acid were added to 2.0 mL of acetone, stirred at room temperature for two days, and centrifuged to obtain a crystalline form A formed by the solid compound of formula (I) and hydrochloric acid.

[0257] Example 15: Preparation of Crystalline Form B Formed by Compound of Formula (I) and Hydrochloric Acid

[0258] 29.2 mg of the compound represented by formula (I) and 55.0 μL of hydrochloric acid were added to 2.0 mL of tetrahydrofuran, stirred at room temperature for two days, and centrifuged to obtain a crystalline form A formed by the solid compound of formula (I) and hydrochloric acid.

[0259] Example 16: Preparation of Crystalline Form A Formed by Compound of Formula (I) and Hydrobromic Acid

[0260] Take about 29.2 mg of the compound represented by formula (I) and 55.0 μL of hydrobromic acid, add them to 1 ml of isopropyl ether / ethanol (v / v=3:1), stir at room temperature for 2 days, centrifuge the suspension, and vacuum dry the solid at room temperature to obtain crystalline form A formed by the compound of formula (I) and hydrobromic acid.

[0261] Example 17: Preparation of Crystalline Form B of the Compound of Formula (I) and Hydrobromic Acid

[0262] 29.2 mg of the compound represented by formula (I) and 55.0 μL of hydrobromic acid were added to 2.0 mL of tetrahydrofuran, stirred at room temperature for two days, and centrifuged to obtain a crystalline form B formed by the solid compound of formula (I) and hydrobromic acid.

[0263] Example 18: Preparation of Crystalline Form A Formed by Compound of Formula (I) and Benzenesulfonic Acid

[0264] 29.2 mg of the compound represented by formula (I) and 8.8 mg of benzenesulfonic acid were added to 1.0 mL of acetone, stirred at room temperature for two days, and centrifuged to obtain a crystalline form A formed by the solid compound of formula (I) and benzenesulfonic acid.

[0265] Example 19: Preparation of Crystalline Form B of the Compound of Formula (I) and Benzenesulfonic Acid

[0266] 29.2 mg of the compound represented by formula (I) and 8.8 mg of benzenesulfonic acid were added to 1.0 mL of tetrahydrofuran, stirred at room temperature for two days, and centrifuged to obtain a crystalline form B formed by the solid compound of formula (I) and benzenesulfonic acid.

[0267] Example 20: Preparation of Crystalline Form A Formed by Compound of Formula (I) and 1,5-Naphthalene Disulfonic Acid

[0268] About 29.2 mg of the compound represented by formula (I) and 15.9 mg of 1,5-naphthalene disulfonic acid were added to 1 ml of isopropyl ether / ethanol (v / v=3:1), and stirred at room temperature for 2 days. The suspension was centrifuged and the solid was vacuum dried at room temperature to obtain a crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid.

[0269] Example 21: Preparation of Crystalline Form B Formed by the Compound of Formula (I) and 1,5-Naphthalene Disulfonic Acid

[0270] Take 29.2 mg of the compound represented by formula (I) and 15.9 mg of 1,5-naphthalene disulfonic acid, add them to 1.0 mL of acetone, stir at room temperature for two days, and centrifuge to obtain a solid crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid.

[0271] Example 22: Preparation of Crystalline Form C Formed by Compound of Formula (I) and 1,5-Naphthalene Disulfonic Acid

[0272] 29.2 mg of the compound represented by formula (I) and 15.9 mg of 1,5-naphthalene disulfonic acid were added to 1.0 mL of tetrahydrofuran, stirred at room temperature for two days, and centrifuged to obtain a crystalline form C formed by the solid compound of formula (I) and 1,5-naphthalene disulfonic acid.

[0273] Crystal form test case

[0274] 1. Instrument information and test method parameter table

[0275]

[0276]

[0277]

[0278]

[0279]

[0280] 2. Specific peak characterization results of XRD tests of each crystal form obtained in the above examples

[0281] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid is as follows: Figure 2 The specific peak values ​​are shown in Table 2.

[0282] Table 2

[0283]

[0284]

[0285]

[0286] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid is as follows: Figure 4 The specific peak values ​​are shown in Table 3.

[0287] Table 3

[0288]

[0289]

[0290] The X-ray powder diffraction pattern (XRD) of the crystalline form C formed by the compound of formula (I) and p-hydroxybenzoic acid is as follows: Figure 6 The specific peak values ​​are shown in Table 4.

[0291] Table 4

[0292]

[0293] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and benzoic acid is as follows: Figure 8 The specific peak values ​​are shown in Table 5.

[0294] Table 5

[0295]

[0296]

[0297]

[0298] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid is as follows: Fig.10 The specific peak values ​​are shown in Table 6.

[0299] Table 6

[0300]

[0301]

[0302] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid is as follows: Fig.12 The specific peak values ​​are shown in Table 7.

[0303] Table 7

[0304]

[0305]

[0306] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and mandelic acid is as follows: Fig.14 The specific peak values ​​are shown in Table 8.

[0307] Table 8

[0308]

[0309] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and methanesulfonic acid is as follows: Fig.16 The specific peak values ​​are shown in Table 9.

[0310] Table 9

[0311]

[0312]

[0313]

[0314] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and methanesulfonic acid is as follows: Fig.18 The specific peak values ​​are shown in Table 10.

[0315] Table 10

[0316]

[0317] The X-ray powder diffraction pattern (XRD) of the crystalline form C formed by the compound of formula (I) and methanesulfonic acid is as follows: Fig. 20 The specific peak values ​​are shown in Table 11.

[0318] Table 11

[0319]

[0320]

[0321] The X-ray powder diffraction pattern (XRD) of the crystalline form D formed by the compound of formula (I) and methanesulfonic acid is as follows: Fig. 22 The specific peak values ​​are shown in Table 12.

[0322] Table 12

[0323]

[0324] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and sulfuric acid is as follows: Fig.24 The specific peak values ​​are shown in Table 13.

[0325] Table 13

[0326]

[0327]

[0328] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and sulfuric acid is as follows: Fig.26 The specific peak values ​​are shown in Table 14.

[0329] Table 14

[0330]

[0331]

[0332] The X-ray powder diffraction pattern (XRD) of the crystalline form AB formed by the compound of formula (I) and hydrochloric acid is as follows: Fig.28 The specific peak values ​​are shown in Table 15.

[0333] Table 15

[0334]

[0335]

[0336] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and hydrochloric acid is as follows: Fig.30 The specific peak values ​​are shown in Table 16.

[0337] Table 16

[0338]

[0339]

[0340] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and hydrobromic acid is as follows: Fig.32 The specific peak values ​​are shown in Table 17.

[0341] Table 17

[0342]

[0343]

[0344] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and hydrobromic acid is as follows: Fig.34 The specific peak values ​​are shown in Table 18.

[0345] Table 18

[0346]

[0347]

[0348]

[0349] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and benzenesulfonic acid is as follows: Fig.36 The specific peak values ​​are shown in Table 19.

[0350] Table 19

[0351]

[0352] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and benzenesulfonic acid is as follows: Fig.38 The specific peak values ​​are shown in Table 20.

[0353] Table 20

[0354]

[0355]

[0356] The X-ray powder diffraction pattern (XRD) of the crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid is as follows: Fig.40 The specific peak values ​​are shown in Table 21.

[0357] Table 21

[0358]

[0359]

[0360] The X-ray powder diffraction pattern (XRD) of the crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid is as follows: Fig.42 The specific peak values ​​are shown in Table 22.

[0361] Table 22

[0362]

[0363] The X-ray powder diffraction pattern (XRD) of the crystalline form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid is as follows: Fig.44 The specific peak values ​​are shown in Table 23.

[0364] Table 23

[0365]

[0366]

[0367] 3. DSC (differential scanning calorimetry) and TGA (thermogravimetric analysis) test results of each crystal form obtained in the above examples

[0368] like Figure 1 As shown, the differential scanning calorimetry curve (DSC) of the crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid shows exothermic and endothermic signals at 174°C and 179°C, and a melting endothermic peak at around 193°C. Its thermogravimetric analysis curve (TGA) shows that the sample has no obvious weight loss during heating to 150°C, and continues to lose weight after 200°C.

[0369] like Figure 3 As shown, the differential scanning calorimetry curve (DSC) of the crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid shows an endothermic and exothermic signal peak at 130-180°C, a melting endothermic peak at about 192°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 3.5% of its weight during heating to 160°C, and continues to lose weight after 200°C.

[0370] As shown in Figure 5, the crystal form is the crystal form C formed by the compound of formula (I) and p-hydroxybenzoic acid, and its differential scanning calorimetry analysis curve (DSC) shows an endothermic signal peak corresponding to TGA weight loss at 120-170°C, a melting endothermic peak at about 192°C, and a thermogravimetric analysis curve (TGA) shows that the sample has an 8.9% weight loss during heating to 160°C, and continues to lose weight after 160°C.

[0371] like Figure 7As shown, the crystal form is crystal form A formed by the compound of formula (I) and benzoic acid, and its differential scanning calorimetry analysis curve (DSC) shows two endothermic signals at around 170°C and 179°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 0.4% weight loss during heating to 120°C and a 11.2% weight loss during heating from 120 to 210°C, which may correspond to the process of decomposition of benzoic acid eutectic and removal of benzoic acid.

[0372] like Fig. 9 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic and exothermic signal peaks at 190-230°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 0.3% weight loss during heating to 150°C, and may decompose after 280°C.

[0373] like Fig.11 As shown, the crystal form is crystal form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 80-150°C, a melting endothermic peak at about 206°C, and a thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 0.3% during heating to 80°C, a weight loss of 2.8% during heating to 80-130°C, and decomposition may occur after 230°C.

[0374] like Fig.13 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and mandelic acid, and its differential scanning calorimetry analysis curve (DSC) shows that there are endothermic signals corresponding to TGA weight loss at 80-120°C and 130-170°C, respectively. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 6.6% during heating to 120°C and a weight loss of 21.6% during heating to 120-220°C, which may correspond to the process of decomposition of mandelic acid eutectic and removal of mandelic acid.

[0375] like Fig.15 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic and exothermic signal peaks at 160-210°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 0.8% weight loss during heating to 140°C, and decomposition may occur after 270°C.

[0376] like Fig.17As shown, the crystal form is the crystal form B formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic and exothermic signals at 120-190°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 6.4% weight loss during heating to 140°C, and decomposition may occur after 280°C.

[0377] like Fig.19 As shown, the crystal form is crystal form C formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic and exothermic signal peaks at 120-200°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 4.7% weight loss during heating to 160°C, and decomposition may occur after 280°C.

[0378] like Fig.21 As shown, the crystal form is the crystal form D formed by the compound of formula (I) and methanesulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 100-140°C, an endothermic signal at 140-160°C, and a thermogravimetric analysis curve (TGA) shows that the sample has an 8.7% weight loss during heating to 140°C, and may decompose after 280°C.

[0379] like Fig.23 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and sulfuric acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic and exothermic signal peaks at 170-210°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 1.7% weight loss during heating to 140°C, and decomposition may occur after 270°C.

[0380] like Fig.25 As shown, the crystal form is the crystal form B formed by the compound of formula (I) and sulfuric acid, and its differential scanning calorimetry curve (DSC) shows that there are endothermic and exothermic signal peaks at 170-210°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a 1.0% weight loss during heating to 120°C, and decomposition may occur after 280°C.

[0381] like Fig. 27 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and hydrochloric acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to the first-order weight loss of TGA at 40-110°C, and an endothermic peak corresponding to the second-order weight loss of TGA at 120-170°C. The thermogravimetric analysis curve (TGA) shows that the sample has an 8.0% weight loss during heating to 100°C and a 5.7% weight loss during heating at 100-180°C, which may correspond to the process of decomposition of the hydrochloride and removal of hydrogen chloride.

[0382] like Fig.29 As shown, the crystal form is the crystal form B formed by the compound of formula (I) and hydrochloric acid, and its differential scanning calorimetry analysis curve (DSC) shows that there is a broad endothermic signal corresponding to the first-order weight loss of TGA at 30-90°C, and an endothermic signal corresponding to the second-order weight loss of TGA at 110-160°C. The thermogravimetric analysis curve (TGA) shows that the sample has an 8.4% weight loss during heating to 90°C and a 14.1% weight loss during heating from 90°C to 160°C, which may include the process of decomposition of hydrochloride and removal of hydrogen chloride.

[0383] like Fig.31 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and hydrobromic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to the first-order weight loss of TGA at 45-110°C, and an endothermic peak at 140-170°C. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 7.6% during heating to 100°C and a weight loss of 12.4% during heating at 100-200°C, which may correspond to the process of decomposition of hydrobromide and removal of hydrogen bromide.

[0384] like Fig.33 As shown, the crystal form is the crystal form B formed by the compound of formula (I) and hydrobromic acid, and its differential scanning calorimetry curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 70-180°C, and the thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 5.5% during heating to 100°C and a weight loss of 17.1% during heating at 100-200°C, which may include the process of decomposition of hydrobromide and removal of hydrogen bromide.

[0385] like Fig.35 As shown, the crystal form is the crystal form A formed by the compound of formula (I) and benzenesulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 30-100°C, and an endothermic signal peak accompanied by exothermic signal at 120-200°C. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 2.5% during heating to 100°C and a weight loss of 1.3% during heating to 170°C, and decomposition may occur after 250°C.

[0386] like Fig.37 As shown, the crystal form is the crystal form B formed by the compound of formula (I) and benzenesulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows that there are two corresponding TGA weight loss endothermic signal peaks at 30-150°C, and an exothermic signal peak at 160-200°C. The thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 2.1% during heating to 100°C, a weight loss of 5.1% during heating at 100-170°C, and continuous weight loss after 250°C.

[0387] like Fig.39 As shown, the crystal form is crystal form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 50-120°C, an endothermic signal at around 282°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 2.3% of its weight during heating to 160°C, and decomposition may occur after 290°C.

[0388] like Fig.41 As shown, the crystal form is the crystal form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 25-120°C, an exothermic signal at 241°C, and a thermogravimetric analysis curve (TGA) shows that the sample loses 7.5% of its weight during heating to 130°C, and decomposition may occur after 280°C.

[0389] like Fig.43 As shown, the crystal form is crystal form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and its differential scanning calorimetry analysis curve (DSC) shows a broad endothermic signal corresponding to TGA weight loss at 40-110°C, an endothermic signal at 230-260°C, and a thermogravimetric analysis curve (TGA) shows that the sample has a weight loss of 10.3% during heating to 110°C, and decomposition may occur after 280°C.

[0390] 4. Stability studies of relevant crystal forms

[0391] The stability of the crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, the crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, the crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid, and the crystalline form B formed by the compound of formula (I) and sulfuric acid was studied under high temperature (60°C), high humidity (25°C / 92.5% RH), light (25°C / 4500Lux), and accelerated (40°C / 75% RH) conditions. Samples were taken for XRPD characterization and HPLC testing at 7 days and 15 days, respectively. The results are shown in Table 24. Figures 45 to 48As shown. XRPD results show that the crystal form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, the crystal form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and the crystal form A formed by the compound of formula (I) and p-hydroxybenzoic acid are all stable under high temperature, high humidity, light, and accelerated conditions for 7 days and 15 days, and the XRPD does not change; the crystal form B formed by the compound of formula (I) and sulfuric acid does not change after being placed under high temperature, light, and accelerated conditions for 7 days and 15 days. HPLC results show that the chemical purity of crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, the crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and the crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid does not change significantly after being placed under high temperature, high humidity and accelerated conditions for 7 days and 15 days; the chemical purity of crystalline form B formed by the compound of formula (I) and sulfuric acid does not change significantly after being placed under high temperature, high humidity, light and accelerated conditions for 7 days and 15 days.

[0392] Table 24 Stability study results

[0393]

[0394]

[0395] Biological test cases

[0396] Test Example 1: USP1 / UAF1 Enzyme Inhibition Activity

[0397] The activity of the deubiquitinase USP1 / UAF1 after drug treatment was detected using ubiquitin rhodamine 110 as a substrate. The total test system was 20 μl, and the test buffer was 50 mM Tris-HCl, pH 7.8, 0.5 mM EDTA, 0.01% Bovine Serum Albumin, 1 mM DTT, 0.01% Tween-20. At the beginning of the test, 0.5 nM USP1 / UAF1 (Bio-Techne, E-568-050) protein was added to a 384-well plate (PerkinElmer, 6008269), and then the gradient dilution of the test compound was added, incubated at room temperature for 10 minutes, and 500 nM ubiquitin rhodamine 110 (Bio-Techne, U-555-050) was added, and incubated at room temperature for 20 minutes. Enspire TM The detection was performed using a Multilabel Reader (PerkinElmer) at an excitation light of 485 nM and an emission light of 535 nM. IC was calculated using GraphPad Prism software. 50 value.

[0398] Table 25 Results of the inhibitory activity of test compounds on USP1 / UAF1 enzyme

[0399] Compound No. <![CDATA[IC 50 (nM)]]> Compound of formula (I) A

[0400] Note: A<20nM

[0401] Conclusion: The compound of formula (I) of the present invention has a good inhibitory effect on the enzymatic activity of USP1 / UAF1.

[0402] Test Example 2: Beagle Dog Pharmacokinetic Test

[0403] Experimental purpose: To administer the test substance to beagle dogs by single-dose intravenous and oral gavage, determine the concentration of the test substance in beagle dog plasma, and evaluate the pharmacokinetic characteristics of the test substance in beagle dogs.

[0404] Experimental animals: Male beagle dogs, about 8-11 kg, purchased from Beijing Mas Biotechnology Co., Ltd.

[0405] Test method: On the day of the test, beagles were randomly divided into groups according to body weight. They were fasted but not watered for 14-18 hours one day before administration, and were fed 4 hours after administration. Administration was performed according to the information in the table below.

[0406]

[0407] Intravenous administration solvent: 5% DMA + 5% Solutol + 90% Saline; intragastric administration solvent: 0.5% MC

[0408] (DMA: dimethylacetamide; Solutol: polyethylene glycol-15-hydroxystearate; Saline: normal saline; MC: methylcellulose solution;)

[0409] Sampling: Blood was collected from the jugular vein or limb vein before and after administration and placed in an EDTAK2 centrifuge tube. The tube was centrifuged at 5000 rpm and 4°C for 10 min to collect plasma.

[0410] Blood collection time: 0, 5min, 15min, 30min, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 24h, 48h, 72h. All samples were stored below -60℃ before analysis. Samples were quantitatively analyzed by LC-MS / MS.

[0411] Table 26 Pharmacokinetic parameters of test compounds in beagle dog plasma

[0412] Test compound Dosage <![CDATA[AUC 0-t (h.ng.mL -1 )]]> F(%) Compound of formula (I) ig (5 mg / kg) 6302 41.2 Control Compound A ig (5 mg / kg) 994 15.8

[0413] * Note: Compounds were administered ig (orally).

[0414] Conclusion: The compound of formula (I) of the present invention has good oral absorption performance in beagle dogs, and its oral performance is better than that of the control compound A, wherein the control compound A is Its preparation method can be found in WO2020132269.

[0415] Test Example 3: MDA-MB-436 cell clone formation test

[0416] This experiment uses MDA-MB-436 cells. After treatment with the test compound, the ability of cell clone formation is detected. At the beginning of the experiment, MDA-MB-436 cells (ATCC, HTB-130) were added to a 96-well plate (Corning, 3599), 500 cells per well, and adhered overnight; the next day, gradient dilutions of the compound were added and the cells were placed in a 37°C, CO2-free incubator for continued culture. On the 7th day, the old culture medium was discarded and the gradient dilutions of the test compound were added again. On the 14th day, the 96-well plate was removed, the culture medium was discarded, and the cell clones were detected using a Crystal violet Assay kit. A PHERAstar FSX microplate reader (BMG LABTECH) was used to analyze the cells at OD 570 Detection at nM. IC was calculated using GraphPad Prism software. 50 value.

[0417] Table 27 Results of the inhibitory activity of test compounds on MDA-MB-436 cell clones

[0418] Compound No. <![CDATA[IC 50 (nM)]]> Compound of formula (I) A

[0419] Note: A<200nM

[0420] Conclusion: The compound of formula (I) of the present invention has a good inhibitory effect on the clone formation of MDA-MB-436 cells.

[0421] Test Example 4: Pharmacokinetics test in mice

[0422] Experimental animals: Male ICR mice, 25-30 g, purchased from Chengdu Dashuo Experimental Animal Co., Ltd.

[0423] Experimental design: On the day of the experiment, ICR mice were randomly divided into groups according to body weight. They were fasted but not watered for 12-14 hours one day before administration and fed 4 hours after administration.

[0424]

[0425] (DMA: dimethylacetamide; Solutol: polyethylene glycol-15-hydroxystearate; Saline: normal saline; MC: methylcellulose)

[0426] Blood was collected from the eye sockets at designated time points before and after administration, placed in EDTAK2 centrifuge tubes, and centrifuged at 5000rpm, 4℃ for 10min to collect plasma. The blood collection time points for the intravenous group and the gavage group were: 0, 5min, 15min, 30min, 1h, 2h, 4h, 7h, 24h. Before analysis and testing, all samples were stored below -60℃, and the samples were quantitatively analyzed by LC-MS / MS.

[0427] Table 28. Pharmacokinetic parameters of test compounds in mouse plasma

[0428] Test compound Dosage Oral absorption Compound of formula (I) ig (10 mg / kg) have

[0429] * Note: Compounds were administered ig (orally).

[0430] Conclusion: The compound of formula (I) of the present invention has good oral absorption performance in mice.

Claims

1. A pharmaceutically acceptable salt or co-crystal of a compound of formula (I):

2. The salt or co-crystal according to claim 1, wherein the pharmaceutically acceptable salt of the compound of formula (I) is selected from methanesulfonate, sulfate, hydrochloride, hydrobromide, benzenesulfonate, 1,5-naphthalene disulfonate; the pharmaceutically acceptable co-crystal of the compound of formula (I) is selected from the co-crystal formed with p-hydroxybenzoic acid, benzoic acid, D(+)-10-camphorsulfonic acid, 3,5-dihydroxybenzoic acid, and mandelic acid.

3. The salt or co-crystal according to claim 1 or 2, which is a crystalline form of a pharmaceutically acceptable salt or co-crystal of a compound of formula (I).

4. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and p-hydroxybenzoic acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.45°±0.2°, 11.77°±0.2°, 11.98°±0.2°, 13.90°±0.2°, 16.39°±0.2°, 17.48°±0.2°, 18.30°±0.2°, 19.23°±0.2°, 19.44°±0.2°, 19.81°±0.2°, 20.05°±0.2°, 23.76°±0.2°, 24.44°±0.2°, 25.10°±0.2°, and 25.91°±0.2°.

5. The crystalline form A according to claim 4, using Cu-Kα radiation, has an X-ray powder diffraction pattern with characteristic diffraction peaks at the following 2θ positions: 5.45°±0.2°, 11.77°±0.2°, 11.98°±0.2°, 12.48°±0.2°, 13.90°±0.2°, 16.39°±0.2°, 17.48°±0.2°, 18. 30°±0.2°, 19.23°±0.2°, 19.44°±0.2°, 19.81°±0.2°, 20.05°±0.2°, 21.97°±0.2°, 22.44°±0.2°, 23.76°±0.2°, 24.44°±0.2°, 25.10°±0.2°, 25.91°±0.2°, 27.02°±0.2°.

6. The crystalline form A according to claim 5, using Cu-Kα radiation, the X-ray powder diffraction pattern of the co-crystal form A is substantially as shown in Figure 2.

7. The crystalline form according to claim 3, which is a crystalline form B formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.87°±0.2°, 17.05°±0.2°, 19.07°±0.2°, 19.50°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 3.87 °±0.2°, 11.26°±0.2°, 11.67°±0.2°, 13.57°±0.2°, 17.05°±0.2°, 18.20°±0.2°, 18.51°±0.2°, 19.07°±0.2°, 19.50°±0.2°, 21.78°±0.2°, 22.20°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 4.

8. The crystalline form according to claim 3, which is a crystalline form C formed by the compound of formula (I) and p-hydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.86°±0.2°, 11.10°±0.2°, 11.53°±0.2°, 16.76°±0.2°, 18.55°±0.2°, 18.76°±0.2°, 19.07°±0.2°, 19.29°±0.2°, 21.08°±0.2°, 21.66°±0.2°, 21.91°±0.2°, 22.11°±0.2°; or has characteristic diffraction peaks at the following 2θ positions Peaks: 3.86°±0.2°, 7.68°±0.2°, 11.10°±0.2°, 11.53°±0.2°, 16.76°±0.2°, 18.30°±0.2°, 18.55°±0.2°, 18.76°±0.2°, 19.07°±0.2°, 19.29°±0.2°, 19.56°±0.2°, 21.08°±0.2°, 21.29°±0.2°, 21.66°±0.2°, 21.91°±0.2°, 22.11°±0.2°, 23.68°±0.2°, 27.39°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 6.

9. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and benzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.16°±0.2°, 5.39°±0.2°, 8.33°±0.2°, 10.15°±0.2°, 14.74°±0.2°, 15.23°±0.2°, 16.49°±0.2°, 17.32°±0.2°, 21.00°±0.2°, 22.75°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 5.16°±0.2°, 5.39°±0.2°, 8.33°±0.2°, 10.15°±0.2°, 14.74°±0.2°, 15.23°±0.2°, 16.49°±0.2°, 17.32°±0.2°, 21.00°±0.2°, 22.75°±0.2°. 8; or its X-ray powder diffraction pattern is substantially as shown in Figure 8.

10. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and D(+)-10-camphorsulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 12.48°±0.2°, 18.33°±0.2°, and 19.75°±0.2°.

11. The crystalline form A according to claim 10, using Cu-Kα radiation, has an X-ray powder diffraction pattern having characteristic diffraction peaks at the following 2θ positions: 7.61°±0.2°, 12.48°±0.2°, 14.97°±0.2°, 15.15°±0.2°, 18.33°±0.2°, 19.75°±0.2°, and 22.61°±0.2°.

12. The crystalline form A according to claim 11, which has an X-ray powder diffraction pattern substantially as shown in Figure 10 using Cu-Kα radiation.

13. The crystalline form according to claim 3, which is crystalline form A formed by the compound of formula (I) and 3,5-dihydroxybenzoic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 14.62°±0.2°, 15.21°±0.2°, and 17.23°±0.2°.

14. The crystalline form A according to claim 13, using Cu-Kα radiation, has an X-ray powder diffraction pattern having characteristic diffraction peaks at the following 2θ positions: 4.89°±0.2°, 14.62°±0.2°, 15.21°±0.2°, 17.23°±0.2°, 18.33°±0.2°, and 25.86°±0.2°.

15. The crystalline Form A according to claim 14, which has an X-ray powder diffraction pattern substantially as shown in Figure 12 using Cu-Kα radiation.

16. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and mandelic acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.55°±0.2°, 7.98°±0.2°, 16.72°±0.2°, 18.43°±0.2°, 19.35°±0.2°, 19.83°±0.2°, 21.87°±0. 2°; or having characteristic diffraction peaks at the following 2θ positions: 5.55°±0.2°, 5.93°±0.2°, 7.98°±0.2°, 16.72°±0.2°, 18.43°±0.2°, 19.35°±0.2°, 19.56°±0.2°, 19.83°±0.2°, 21.44°±0.2°, 21.87°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 14.

17. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.29°±0.2°, 16.97°±0.2°, 17.71°±0.2°, 21.06°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 5.29°±0.2°, 8.68°±0.2°, 14.21°±0.2°, 16.18°±0.2°, 16.97°±0.2°, 17.71°±0.2°, 21.06°±0.2°, 25.99°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 16; Alternatively, it is a crystalline form B formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.57°±0.2°, 7.72°±0.2°, 11.09°±0.2°, 22.20°±0.2°; or it has characteristic diffraction peaks at the following 2θ positions: 5.57°±0.2°, 7.72°±0.2°, 11.09°±0.2°, 16.10°±0.2°, 17.03°±0.2°, 19.19°±0.2°, 20.01°±0.2°, 22.20°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 18. Alternatively, it is a crystalline form C formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 4.57°±0.2°, 9.01°±0.2°, 9.18°±0.2°, 17.48°±0.2°; or it has characteristic diffraction peaks at the following 2θ positions: 4.57°±0.2°, 9.01°±0.2°, 9.18°±0.2°, 9.63°±0.2°, 9.84°±0.2°, 17.17°±0.2°, 17.48°±0.2°, 20.26°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 20. Alternatively, it is a crystalline form D formed by the compound of formula (I) and methanesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.51°±0.2°, 11.07°±0.2°; or its X-ray powder diffraction pattern is basically as shown in Figure 22.

18. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and sulfuric acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.82°±0.2°, 16.43°±0.2°, 20.78°±0.2°, 23.47°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 4.63°±0.2°, 5.82°±0.2°, 16.43°±0.2°, 17.54°±0.2°, 18.43°±0.2°, 20.08°±0.2°, 20.78°±0.2°, 23.47°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 24.

19. The crystalline form according to claim 3, which is a crystalline form B formed by the compound of formula (I) and sulfuric acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.99°±0.2°, 14.45°±0.2°, 15.56°±0.2°, and 23.66°±0.2°.

20. The crystalline form B according to claim 19, using Cu-Kα radiation, has an X-ray powder diffraction pattern having characteristic diffraction peaks at the following 2θ positions: 5.99°±0.2°, 6.28°±0.2°, 7.30°±0.2°, 14.45°±0.2°, 15.56°±0.2°, 20.05°±0.2°, 20.98°±0.2°, and 23.66°±0.2°.

21. The crystalline Form B according to claim 20, which has an X-ray powder diffraction pattern substantially as shown in Figure 26 using Cu-Ka radiation.

22. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and hydrochloric acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 8.27°±0.2°, 9.39°±0.2°, 15.61°±0.2°, 20.20°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 7.96°±0.2°, 8.27°±0.2°, 9.39°±0.2°, 15.61°±0.2°, 17.65°±0.2°, 20.20°±0.2°, 23.82°±0.2°, 26.30°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 28. Or it is a crystalline form B formed by the compound of formula (I) and hydrochloric acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 12.31°±0.2°, 17.95°±0.2°, 23.70°±0.2°, 25.60°±0.2°; or it has characteristic diffraction peaks at the following 2θ positions: 3.39°±0.2°, 3.80°±0.2°, 12.31°±0.2°, 12.82°±0.2°, 17.95°±0.2°, 23.70°±0.2°, 25.60°±0.2°, 26.03°±0.2°; or its X-ray powder diffraction pattern is basically as shown in Figure 30.

23. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and hydrobromic acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 3.54°±0.2°, 4.83°±0.2°, 10.02°±0.2°, 20.71°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 3.54°±0.2°, 4.59°±0.2°, 4.83°±0.2°, 10.02°±0.2°, 14.39°±0.2°, 20.59°±0.2°, 20.71°±0.2°, 22.49°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 32. Alternatively, it is a crystalline form B formed by the compound of formula (I) and hydrobromic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.63°±0.2°, 22.18°±0.2°, 23.56°±0.2°, 25.25°±0.2°; or it has characteristic diffraction peaks at the following 2θ positions: 6.63°±0.2°, 16.18°±0.2°, 22.18°±0.2°, 23.56°±0.2°, 25.25°±0.2°, 26.56°±0.2°, 26.96°±0.2°, 28.13°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 34.

24. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and benzenesulfonic acid, using Cu-Kα radiation, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 5.92°±0.2°, 6.65°±0.2°, 10.64°±0.2°, 13.20°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 5.60°±0.2°, 5.92°±0.2°, 6.65°±0.2°, 10.64°±0.2°, 11.80°±0.2°, 13.20°±0.2°, 20.18°±0.2°, 20.53°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 36. Alternatively, it is a crystalline form B formed by the compound of formula (I) and benzenesulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.09°±0.2°, 7.28°±0.2°, 12.13°±0.2°, 19.42°±0.2°; or it has characteristic diffraction peaks at the following 2θ positions: 6.09°±0.2°, 7.28°±0.2°, 10.89°±0.2°, 12.13°±0.2°, 12.43°±0.2°, 19.42°±0.2°, 20.36°±0.2°, 21.79°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 38.

25. The crystalline form according to claim 3, which is a crystalline form A formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 9.10°±0.2°, 11.14°±0.2°, 18.70°±0.2°, 21.43°±0.2°; or has characteristic diffraction peaks at the following 2θ positions: 9.10°±0.2°, 11.14°±0.2°, 17.30°±0.2°, 18.70°±0.2°, 20.43°±0.2°, 21.43°±0.2°, 23.08°±0.2°, 25.95°±0.2°; or its X-ray powder diffraction pattern is substantially as shown in Figure 40. Or it is a crystalline form B formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 7.43°±0.2°, 22.03°±0.2°, 22.42°±0.2°, 22.92°±0.2° or has characteristic diffraction peaks at the following 2θ positions: 7.43°±0.2°, 9.86°±0.2°, 17.81°±0.2°, 19.27°±0.2°, 20.80°±0.2°, 22.03°±0.2°, 22.42°±0.2°, 22.92°±0.2°; or its X-ray powder diffraction pattern is basically as shown in Figure 42. Or it is a crystalline form C formed by the compound of formula (I) and 1,5-naphthalene disulfonic acid, and using Cu-Kα radiation, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions: 6.62°±0.2°, 6.77°±0.2°, 6.87°±0.2°, 9.71°±0.2°; or it has characteristic diffraction peaks at the following 2θ positions: 6.62°±0.2°, 6.77°±0.2°, 6.87°±0.2°, 7.22°±0.2°, 9.57°±0.2°, 9.71°±0.2°, 19.58°±0.2°, 19.77°±0.2°; or its X-ray powder diffraction pattern is basically as shown in Figure 44.

26. A pharmaceutical composition comprising a therapeutically effective amount of the salt, co-crystal or crystalline form according to any one of claims 1 to 25, and a pharmaceutically acceptable carrier and / or excipient, wherein the therapeutically effective amount is preferably 1-1500 mg.

27. Use of the salt, co-crystal or crystalline form of any one of claims 1 to 25, or the pharmaceutical composition of claim 26, in the preparation of a medicament for treating tumors associated with USP1.

28. A method for treating a tumor disease associated with USP1, the method comprising administering to a subject a therapeutically effective amount of the salt, cocrystal or crystal form of any one of claims 1 to 25, the therapeutically effective amount is preferably 1 to 1500 mg, and the disease is preferably a tumor.

Citation Information

Patent Citations

  • Substituted pyrazolopyrimidines and substituted purines and their use as ubiquitin-specific-processing protease 1 (USP1) inhibitors

    WO2020132269A1

Cited By

  • Crystal form of pyridopyrazole derivative and preparation method therefor and use thereof

    WO2026026740A1